A comparative study of anti-aging properties and mechanism: resveratrol and caloric restriction - Li, Juan (Oncotarget, 2017)
Resveratrol and caloric restriction (CR) are the powerful therapeutic options for anti-aging. Here, their comparative effect on longevity-associated gene silencing information regulator (SIRT1) were evaluated in vitro and in vivo. IMR-90 cells treated with 2,2’-azobis (2-amidinopropane) dihydrochloride (AAPH) were applied to establish a cellular senescence model, and rats treated with D-galactose (D-gal) were used as an aging animal model. Resveratrol and CR exhibited similar anti-aging activities, evidenced by inhibiting senescence and apoptosis, and restoring cognitive impairment and oxidative damage. Moreover, they could up-regulate telomerase (TE) activity, increase expressions of SIRT1, forkhead box 3a (Foxo3a), active regulator of SIRT1 (AROS) and Hu antigen R (HuR ), but decrease p53 and deleted in breast cancer 1 (DBC1) levels. However, 10 μM resveratrol in vitro and the high dose group in vivo showed relatively stronger activities of anti-aging and stimulating SIRT1 level than CR. In conclusion, resveratrol and CR showed similar anti-aging activities on SIRT1 signaling, implicating the potential of resveratrol as a CR mimetic.